Trend changes in disease burden of lower respiratory infections among children under 5 years of age in the world, high SDI countries, and China from 1990 to 2019 - an analysis of GBD 2019 data - Yan WANG; Junli CHEN; Wenjia FENG; Xiao DING; Ruiyang HAN; Anning MA (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo understand the trend changes in the burden of lower respiratory infections (LRIs) among children aged < 5 years in the world, high socio-demographic index (SDI) countries, and China from 1990 to 2019, to provide reference for the formulation and timely adjustment of LRIs prevention and control strategies for children, and to evaluate the effect of prevention and treatment measures. MethodsData on the burden of LRIs among children aged < 5 years in the world, high SDI countries, and China from 1990 to 2019 were collected from the Global Burden of Disease Study 2019 (GBD 2019) database. Descriptive analysis was performed using indicators such as incidence rate, mortality rate, and disability-adjusted life-year (DALY) rate. Joinpoint regression model was used to analyze the trend changes in the burden of LRIs. ResultsAmong children aged < 5 years in the world, high SDI countries, and Chin, the incidence rate (1/100 000) of LRIs decreased from 14 129.55, 6 619.66, and 14 492.75 in 1990 to 6 801.55, 5 064.93, and 4 134.33 in 2019, with the annual average percentage change (AAPC) of - 2.49%, - 0.91%, and - 4.23% (all P < 0.05); the mortality rate (1/100 000) of LRIs decreased from 349.48, 9.22, and 336.63 in 1990 to 101.37, 2.27, and 18.10 in 2019, with AAPC of - 4.21%, - 4.74%, and - 9.67% (all P < 0.05); and the DALY rate (1/100 000) decreased from 30 726. 35, 820.29, and 29 660.06 in 1990 to 8 925.53, 206.76, and 1 602.53 in 2019, respectively, with the AAPC of - 4.20%, - 4.66%, and - 9.63% (all P < 0.05). The age-specific incidence rate, mortality rate, and DALY rate of LRIs among children aged < 5 years in the world, high SDI countries, and China all showed a decreasing trend from 1990 to 2019 (all P < 0.05), with the highest burden in newborns aged 0 - 6 days and 7 - 27 days, and the lowest burden in children aged 1 - 4 years. ConclusionThe burden of LRIs among children aged < 5 years in the world, high SDI countries and China showed a decreasing trend from 1990 to 2019, but the burden in newborns remained high. Prevention and control of LRIs in newborns should be strengthened to further reduce the burden of LRIs among children aged < 5 years.